Halal Certification and Branding : Unlocking The Potential of SMEs in The Islamic Economy - Asmara, Maisa Azizah; Arissaputra, Rivaldi; Nur Sabila, Sherly; Aprila, Dikri Sillmi (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to empower Micro and Small Enterprises (MSEs) under the guidance of MEK ’Aisyiyah Jawa Barat through halal certification and halal branding to enhance product competitiveness and expand market access. The implementation method consists of three stages: (1) Preparation, which includes needs assessment and material development; (2) Implementation, encompassing counselling, technical assistance, and training; and (3) Evaluation, involving pre-test and post-test analysis. The data collected is subsequently analyzed using descriptive methods by comparing pre- and post-test percentages to identify improvements in participantsâ€™ knowledge, attitudes, and skills. The core activities include counselling on halal certification, assistance in creating a self-declaration-based SIHALAL account, training in logo design using Canva, and support in setting up a GoBiz account for digital marketing. Post-test results demonstrated significant improvements in participants’ knowledge, attitudes, and skills. The program successfully enhanced participantsâ€™ understanding of halal branding and certification while broadening market opportunities through the integration of digital technology. Key recommendations include sustained mentoring, in-depth technical training, and collaboration with relevant stakeholders to ensure the programâ€™s long-term impact and sustainability.